Stress response of European seabass (Dicentrarchus labrax) fed plant-based diets supplemented with swine blood hydrolysates - Resende, Daniela (2023)
To improve fish welfare, it is essential that aquafeeds are designed to help fish cope with the stressful conditions of fish farms. One effective strategy to achieve this goal is to supplement the diet with bioactive hydrolysates. Here, diet supplementation to modulate oxidative stress after air exposure was investigated in European seabass, using swine blood hydrolysates (BH), obtained either by autohydrolysis (AH) or enzymatically. The enzymatically produced BH were further submitted to a micro- (RMF) and nanofiltration (RNF). Four isolipidic, isoproteic and isoenergetic diets were developed: a plant-based diet with low (12.5%) fishmeal levels (control, CTRL) and three diets where 3% of each BH (RMF, RNF and AH) was added to the CTRL. Diets were assigned to triplicate groups of 71 European seabass juveniles (initial weight 12.3 ± 1.4 g). After 12 weeks, 9 fish per treatment were either immediately sampled or air-exposed for 1 min and let to recover in a new system for 6 h prior to sampling. Stress response increased cortisol levels, followed by an increment in plasma lactate. The challenge increased liver lipid peroxidation (LPO) due to reactive oxygen species (ROS) accumulation. Carbonyls decreased post-stress, maybe due to a possible interaction with the LPO radicals, reducing protein oxidation. None of the BH improved plasma stress response. By reducing catalase levels without increasing LPO, the RNF treatment appears to adjust European seabass' antioxidant defences, indicating its potential to supply exogenous antioxidants to combat oxidative stress induced by ROS. However, this impact was not sufficient to lower LPO levels compared to a control plant-based diet. The tested diets seemed to affect the fish oxidative stress response in the liver, possibly due to the presence of bioactive peptides, which aided in the non-enzymatic modulation of stress response, as observed by the total antioxidant capacity values in the liver.